2011
DOI: 10.1016/j.bbr.2010.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Environmental noise affects auditory temporal processing development and NMDA-2B receptor expression in auditory cortex

Abstract: Auditory temporal processing is essential for sound discrimination and speech comprehension. Under normal developmental conditions, temporal processing acuity improves with age. As recent animal studies have shown that the functional development of the auditory cortex (AC) is impaired by early life exposure to environmental noise (i.e., continuous, moderate-level, white noise), here we investigated whether the normal age-related improvement in temporal processing acuity is sensitive to delayed development of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 31 publications
2
29
1
1
Order By: Relevance
“…As adults, these animals actually display poor discrimination at the exposed frequency, yet their discrimination of adjacent frequencies is significantly better than controls (Han et al, 2007). In contrast, when young animals are exposed to noise for days or weeks, behavioral measures typically reveal diminished or delayed capacities (Philbin et al, 1994; Zhang et al, 2008; Zhou and Merzenich, 2009; Sun et al, 2011). Because the tone or noise levels used in these experiments appear to be too low to injure the cochlea, the behavioral impact is likely attributable to central changes (below).…”
Section: Early Auditory Experience Influences Perceptual Skillsmentioning
confidence: 99%
“…As adults, these animals actually display poor discrimination at the exposed frequency, yet their discrimination of adjacent frequencies is significantly better than controls (Han et al, 2007). In contrast, when young animals are exposed to noise for days or weeks, behavioral measures typically reveal diminished or delayed capacities (Philbin et al, 1994; Zhang et al, 2008; Zhou and Merzenich, 2009; Sun et al, 2011). Because the tone or noise levels used in these experiments appear to be too low to injure the cochlea, the behavioral impact is likely attributable to central changes (below).…”
Section: Early Auditory Experience Influences Perceptual Skillsmentioning
confidence: 99%
“…The physiological function of the IC is largely affected by the excitatory and inhibitory signals mediated by glutamatergic and GABAergic projections. Lack of GABAergic inhibition in the IC is involved in different auditory disorders, including tinnitus, hyperacusis (Brozoski et al, 2007; Dong et al, 2010), and audiogenic seizure (Sun et al, 2011). Previous studies have indicated that a restricted lesion in the cochlea can cause a substantial reduction in GABAergic inhibition within the IC, which may cause increased responsiveness of neurons at the nondamaged frequencies (Gerken, 1996; Felix and Portfors, 2007).…”
mentioning
confidence: 99%
“…Importantly, the degraded spatial hearing could be restored by additional behavioral training. In the work of Sun et al (2011), adult rats reared in environmental noise (starting from P7) exhibited a degraded temporal processing acuity compared to controls. However, in this case, the poorer temporal processing acuity represented not a permanent impairment, but rather a delayed development, as placing the noise-reared animals in normal housing conditions improved their gap detection threshold to a normal level.…”
Section: Behavioral Consequences Of Early Sound Exposurementioning
confidence: 98%
“…It appears that even a short-time detachment of the developing auditory system from natural and rich auditory experience, resulting from an impaired periphery or anomalous stimulation such as noise or clicks, will often result in altered structural and functional characteristics at various levels of the auditory system. These changes may comprise, for example, a decrease in the number of hair cells and their ribbon synapses Shi et al, 2015), abnormal dendritic trees and cell sizes of neurons in the central auditory system (Gabriele et al, 2000;Ouda et al, 2014;Lu et al, 2014), altered neuronal responsiveness and representation of stimulus frequency and intensity (e.g., Zhang et al, 2001;Gr ecov a et al, 2009;Bure s et al, 2010;Insanally et al, 2010), or deteriorated psychophysical, behavioral and cognitive functions (Rybalko et al, 2011;Sun et al, 2011;Pan et al, 2011;Rybalko et al, 2015;Suta et al, 2015;RuvalcabaDelgadillo et al, 2015). Despite this volume of work, there still exists great uncertainty as to what effect a specific intervention will have: different interventions may have different consequences at various levels of the auditory system, depending also on the type of intervention, stimulus type, exposure levels, or age of exposure (e.g., Sanes and Constantine-Paton, 1985;Zhang et al, 2001;Chang et al, 2005;Gr ecov a et al, 2009;Insanally et al, 2009;Miyakawa et al, 2013).…”
Section: Introductionmentioning
confidence: 97%